Sense of community coherence and inter-religious relations. Issue 5 (2nd September 2016) - Mana, Adi; Sagy, Shifra; Srour, Anan
ABSTRACT: The current article attempts to broaden the individual-based concept of sense of coherence to the community level. We examine sense of community coherence and its connection with perceptions of collective narratives and acculturation tendencies in the social context of Palestinian Muslims and Christians living in Israel. Questionnaires that were developed and adapted for the unique population in this study were distributed to a representative sample of 1034 Muslims (455 males) and 720 Christians (354 males), all Israeli citizens aged 18 and up. As expected, sense of community coherence was negatively related to the level of acceptance of the out-group collective narratives and positively related to the level of acceptance of the in-group collective narratives. In the same vein, it was also positively related to the tendency for separation and negatively related to the tendency for integration and assimilation. The discussion focuses on the contribution of the research findings to the deepening of our understanding of the concepts of sense of coherence and sense of community coherence.